2018
DOI: 10.1177/2382120518790257
|View full text |Cite
|
Sign up to set email alerts
|

Simulated Encounters With Vaccine-Hesitant Parents: Arts-Based Video Scenario and a Writing Exercise

Abstract: Vaccine hesitancy is an increasing and urgent global public health challenge. Medical students’ encounters with vaccine-hesitant parents, however, remain incidental and unexplored. During pre-clinical training, the vaccine-hesitant parents are typically represented through impersonal text-based cases, lists of their concerns, and sometimes a virtual patient. However, in reality, vaccine-hesitant parents have many health beliefs and arguments that are accompanied with intense emotions, and students remain unawa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 37 publications
0
19
0
Order By: Relevance
“…When considering the impact of the documentary, its main aim was to expose medical students to reallife parents and their noncompliance to medical advice. The film has thus far been employed in two medical schools' curriculum, and the students' responses have been studied through qualitative analysis (Koski, Lehto, and Hakkarainen 2018). Other audiences' responses have not been recorded or further examined; however, the film reaches out to a variety of different scientific and artistic contexts internationally.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When considering the impact of the documentary, its main aim was to expose medical students to reallife parents and their noncompliance to medical advice. The film has thus far been employed in two medical schools' curriculum, and the students' responses have been studied through qualitative analysis (Koski, Lehto, and Hakkarainen 2018). Other audiences' responses have not been recorded or further examined; however, the film reaches out to a variety of different scientific and artistic contexts internationally.…”
Section: Discussionmentioning
confidence: 99%
“…This documentary has been screened in several festivals and exhibitions, but its primary audience comprises medical students. I designed a writing exercise, together with the film screening and related discussions, as an educational intervention and conducted a pilot study on this intervention with my clinical teacher collaborators (Koski, Lehto & Hakkarainen 2018). The intention of this phase of the project was to prepare medical students to respond to different health beliefs and non-compliance in a respectful manner.…”
Section: Introductionmentioning
confidence: 99%
“…A review of literature related to vaccine education identified what was known and gaps to fill through this educational initiative. [20][21][22][23][24][25][26] Step 2. Targeted Needs Assessment With the rapidly evolving knowledge in the scientific community around COVID-19 vaccines, the group decided to target education to pediatric clinicians.…”
Section: Step 1 General Needs Assessmentmentioning
confidence: 99%
“…There are only a few published reports of educational interventions that focus on specifically teaching medical students' communication skills for counseling vaccine-hesitant patients and parents. These range from an art-based video format helping preclinical students reflect on the health beliefs raised by vaccine-hesitant parents [8] to flipped classroom and case-based format for third-year students [9]. Schnaith et al showed an educational intervention followed by role-play resulted in an increase in student awareness about the HPV vaccine as well as improved student comfort level discussing this with vaccine-hesitant parents [10].…”
Section: Introductionmentioning
confidence: 99%